Myo/Nog cells expressing muscle proteins are present in preretinal membranes from patients with proliferative vitreoretinopathy. (August 2020) - Gerhart, Jacquelyn; Morrison, Nathan; Gugerty, Lindsay; Telander, David; Bravo-Nuevo, Arturo; George-Weinstein, Mindy
Abstract: Proliferative vitreoretinopathy (PVR) is a complication of rhegmatogenous retinal detachment and ocular trauma. The disease is characterized by development of membranes that may apply traction to the retina and cause redetachment. Membrane contractions are attributed to myofibroblasts arising from retinal pigment epithelial cells, glia and fibroblasts. The progenitors of myofibrobasts in the lens are Myo/Nog cells that express the skeletal muscle transcription factor MyoD and bone morphogenetic protein inhibitor Noggin. The retina and choroid also contain Myo/Nog cells that respond to stress. We examined preretinal PVR membranes from three ocular trauma patients with retinal detachment for Myo/Nog cells and their expression of muscle proteins. Myo/Nog cells were identified by co-localization of antibodies to the G8 antigen and Noggin. Greater than 80% of all cells in sections from two of three patients expressed both G8 and Noggin. Myo/Nog cells lacked pigment. Alpha smooth muscle actin (α-SMA) and striated myosin II heavy chain were present in the majority of Myo/Nog cells in these two patients. Differentiation of Myo/Nog cells was paralleled by low levels of MyoD. Membrane sections from the third patient consisted mostly of connective tissue with very few cells. A small subpopulation in these sections expressed both G8 and Noggin, and muscle proteins were detected in only a minority of G8-positive (+) cells. In all three patients, greater than 99% of cells with MyoD, α-SMA and striated muscle myosin co-expressed G8. These findings suggest that contractile myofibroblasts in PVR membranes may be derived from differentiating Myo/Nog cells.